KRITERIA TANDA PUBLIC DOMAIN YANG DIGUNAKAN SEBAGAI MEREK (Lex Journal: Kajian Hukum & Keadilan, 2018)
This study examines the Criteria for Signs of Public Domain Used as a Brand. This research is legal research by using a method that is in accordance with the scientific characteristics of Law (jurisprudence), namely normative legal research. Concluded also some signs of criteria in the Public Domain Trademark law, namely: Public Domain because it is over the protection period, the Public Domain for distinguishing the substantive requirements are not met. (Article 20 letter (f) UU No. 16/2016 on Trademarks and Geographical Indications), Public Domain because it includes the area of public property, Public Domain because it does not open rivalry, Public Domain because it includes Public Knowledge. Public Domain since its birth, Public Domain because of government policy, Public Domain because something that can be enjoyed by everyone at any time, Public Domain because it is a public good, and Public Domain because there is no scarcity and is available to all